Altitude and team-sport athlete physical performance: Relevance and time course for adaptation - Inness, M. W. H. (Victoria University, 2017)
Team-sport competition is intermittent in nature, with large amounts of low to moderate intensity activity interspersed with periods of repeated high intensity efforts. As well as the locomotor distance, there are game involvements that require excellent strength and power with a high metabolic cost. Therefore, team-sport athletes need a unique mixture of strength, power, speed, endurance, and intermittent running ability. Altitude training can improve endurance and repeat sprint performance. There is also the potential to increase strength and hypertrophy when resistance training is performed in hypoxia. Taken together, these findings suggest that altitude training has the potential to increase team-sport athlete running performance, however, there is still a number of questions to investigate before establishing more precise guidelines of implementation for team-sport athletes. The aim of this PhD thesis is to determine whether altitude training improves running performance in team-sport athletes, the time course for any adaptation and how long the benefits remain in this population.